Author Correction: Zebrafish as an animal model in epilepsy studies with multichannel EEG recordings. Issue 1 (December 2017) - Cho, Sung-Joon; Byun, Donghak; Nam, Tai-Seung; Choi, Seok-Yong; Lee, Byung-Geun; Kim, Myeong-Kyu; Kim, Sohee
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.